Réponses

2013-01-15T19:36:02+01:00

sin (3x - pi/3) = cos (pi/2 - 3x + pi/3) = cos(5pi/6 - 3x)

 

cos(5pi/6 - 3x) = cosx

5pi/6 - 3x = +ou - x + k2pi

avec +                                                   avec -

5pi/6 - 3x = x + k2pi                               5pi/6 - 3x = -x + k2pi                                                      

-4x =  -5pi/6 + k2pi                                          -2x = -5pi/6 + k2pi

x =  5pi/24 + k2pi/4 (4 solutions)                       x = 5pi/12 + kpi   (2 solutions)